Hybrid Nanocomposite Mini-Tablet to Be Applied into the Post-Extraction Socket: Matching the Potentialities of Resveratrol-Loaded Lipid Nanoparticles and Hydroxyapatite to Promote Alveolar Wound Healing - Viviana De Caro; Giada Tranchida; Cecilia La Mantia; Bartolomeo Megna; Giuseppe Angellotti; Giulia Di Prima (Pharmaceutics)
Background/Objectives: Following tooth extraction, resveratrol (RSV) can support healing by reducing inflammation and microbial risks, though its poor solubility limits its effectiveness. This study aims to develop a solid nanocomposite by embedding RSV in lipid nanoparticles (mLNP) within a hydrophilic matrix, to the scope of improving local delivery and enhancing healing. Hydroxyapatite (HXA), often used as a bone substitute, was added to prevent post-extraction alveolus volume reduction. Methods: The mLNP-RSV dispersion was mixed with seven different polymers in various mLNP/polymer ratios. Following freeze-drying, the powders were redispersed, and the resulting dispersions were tested by DLS experiments. Then, the best two nanocomposites underwent extensive characterization by SEM, XRD, FTIR, Raman spectroscopy, and thermal analysis as well as in vitro partitioning studies aimed at verifying their ability to yield the mLNP-RSV from the hydrophilic matrix to a lipophilic tissue. The characterizations led to identify the best nanocomposite, which was further combined with HXA to obtain hybrid nanocomposites, further evaluated as pharmaceutical powders or in form of mini-tablets. Results: PEG-based nanocomposites emerged as optimal and, following HXA insertion, the resulting powders revealed adequate bulk properties, making them useful as a pharmaceutical intermediate to produce ≈59 mm3 mini-tablets, compliant with the post-extraction socket. Moreover, they were proven ex vivo to be able to promote RSV and GA accumulation into the buccal tissue over time. Conclusions: The here-proposed mini-tablet offers an innovative therapeutic approach for alveolar wound healing promotion as they led to a standardized dose administration, while being handy and stable in terms of physical solid identity as long as it takes to suture the wound.